Pandemic potential of henipaviruses - Aleksandra Wojtkiewicz; Maciej Szota; Kornelia Kędziora–Kornatowska (Journal of Medical Science, 2023)
Introduction and purpose. Hendra and Nipah are two highly dangerous zoonotic viruses belonging to the group of henipaviruses. Although they have been known for more than 20 years, no human drug or vaccine has been invented for them. The aim of this paper is to describe the epidemiology of the reported paramyxoviruses, the pandemic potential of henipaviruses and a standardised action plan to counter their spread. This paper is a review of scientific articles from 2012-2023 published in the scientific databases such as Pubmed, Researchgate and Google Scholar. The following keywords were used: pandemic potential of henipaviruses, Hendra virus, Nipah virus, henipavirus epidemics.